Measuring Stability period of post-closure sanitary landfill in Malaysia using double exponential smoothing - Noor Ezlin Ahmad Basri,; Hassan Basri,; Wan Siti Adibah Wan Dahalan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The stability period for post-closure dump and landfill sites in Malaysia is of least concern among scholars and policy makers. The current policy to manage these sites are based on the conventional practices by the local authorities and agencies which do not take into account the sustainability or how environmentally friendly these practices are. The aims of this paper are to identify the most suitable forecasting method for time series data of CO2 emission, to conduct simulation exercise to indicate the stability period of sanitary landfill by using the CO2 emission, and to examine the current policy for the post-closure landfill sites and its current practice in the country. Datasets were obtained from literature and simulation was conducted for the Air Hitam Sanitary Landfill, Puchong, Selangor. The results indicate that the Double Exponential Smoothing is the most suitable forecasting method and another 120 years are required for the gas emission to reach stability, which is in September 2127. The current policy on post-closure dump and landfill sites in Malaysia are explored and other potential options are also discussed.